A biorefinery from Nannochloropsis sp. microalga – Energy and CO2 emission and economic analyses - Ferreira, Ana F. (2013)
Are microalgae a potential energy source for biofuel production? This paper presents the laboratory results from a Nannochloropsis sp. microalga biorefinery for the production of oil, high-value pigments, and biohydrogen (bioH2). The energy consumption and CO2 emissions involved in the whole process (microalgae cultivation, harvest, dewater, mill, extraction and leftover biomass fermentation) were evaluated. An economic evaluation was also performed. Oil was obtained by soxhlet (SE) and supercritical fluid extraction (SFE). The bioH2 was produced by fermentation of the leftover biomass. The oil production pathway by SE shows the lowest value of energy consumption, 177-245 MJ/MJprod, and CO2 emissions, 13–15 kgCO2/MJprod. Despite consuming and emitting c.a. 20% more than the SE pathway, the oil obtained by SFE, proved to be more economically viable, with a cost of 365€/kgoil produced and simultaneously extracting high-value pigments. The bioH2 as co-product may be advantageous in terms of product yield or profit.